PREGNANCY AND CHILDBIRTH IN PATIENTS WITH RENAL ALLOGRAFT (CASE REPORT) - R. R. Temirbulatov; V. F. Bezhenar; O. N. Reznik; A. N. Anan’ev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Relevance. Kidney transplantation is the method of choice for women of reproductive age with late stage of chronic kidney disease, who want to realize their  childbearing function. Pregnancy and childbirth in patients with renal  allografts are classified as an increased risk due to the more frequent complications compared to the general population. Progressive pregnancy is observed in 5–12 % of patients with renal  allograft, the frequency of favorable outcomes in such  cases  is 65–92 %.Objective. To identify the most common complications in pregnancy in women with a transplanted kidney, to review the algorithms for maintaining this category of patientsMaterial and methods. In the  clinic  of obstetrics and  gynecology two patients with a renal  allograft were examined and  delivered, observed in common with specialists from the Research Institute of Surgery and Urgent Medicine.Results. Both patients were delivered by a cesarean section, the postoperative period proceeded without complications in both cases.Conclusions. This  category of patients needs to be  closely monitored throughout the  pregnancy by a multidisciplinary team  of specialists. This article describes the clinical cases  of pregnancy in patients with a transplanted kidney.